A Study on the Role of the Judicial Committee in Nepal to Ensure Women’s Access to Justice - Shrestha, Tej Man; Maharjan, Rukamanee; Raut, Balram Prasad (KDCBAR Law Journal, 2025)
Access to justice is a fundamental principle and a pre-requisite for ensuring equal protection of law and effective remedy. However, in Nepal, it is argued that women do not enjoy equal protection of law and subsequently, access to justice and effective remedy. This is particularly true for rural women in Nepal. With the federalism in Nepal, local judicial committees have come to existence as a judicial forum closer to local people that understand local contexts and is accessible for women and other vulnerable population. This paper explores the link between these committees and women’s access to justice. It includes a case study of Bagmati Province where 332 service seekers from the Committees were surveyed regarding the role of the Judicial Committee in improving women’s access to justice.